Cross-cultural insights into internet addiction and mental health: a network analysis from China and Malawi - Mengze Li; Yidi Wang; Bin Liu; Xiaoli Ni; Zhujing Ma; Fengzhan Li; Tifei Yuan; Hongyi Chen; Zhongying Wu; Qiannan Jia; Lei Song; Yinchuan Jin; et al. (BMC Public Health)
Abstract Background Internet addiction has emerged as a significant mental health issue among university students. The study aimed to compare the network structures of Internet addiction and mental health symptoms among university students in China and Malawi, which provide insights into culturally sensitive prevention and intervention strategies. Methods Network analysis was used on two datasets: Malawi (n = 688) and China (n = 975) using the Internet Addiction Test and the Self-Reporting Questionnaire. Network estimation, centrality, bridge estimation and network comparison, were conducted using R software. Results The prevalence of internet addiction and mental health was significantly higher in China than Malawi. In Malawi, the strongest edges were “school work” - “job performance” and “worthless” - “unable to play a useful part”. The central nodes were “daily work suffering”, “fantasize” and “lost interest”. In China, the strongest edges were “neglect household” - “neglect partner” and “difficult to enjoy” - “daily work suffering”. The central nodes were “trouble thinking”, “unhappiness”, and “unable to play a useful part”. Bridge symptoms varied between the countries, with functional impairments (school work, daily work suffering and difficult to make decision) being more prominent in Malawi and emotional disturbances (daily work suffering, act annoyed and difficult to enjoy) in China. Conclusions The study highlights significant differences in the network structures of internet addiction and mental health between China and Malawi, which underscore the importance of culturally sensitive mental health interventions. In Malawi, addressing functional impairments related to academic and work performance is crucial, while in China, interventions should focus on emotional and relational aspects.